Changing Pacific Masculinities: The ‘Problem’ of Men - Taylor, John P. (The Australian journal of anthropology, 2008)
This introduction places the papers of this Special Issue within the context of a brief overview of previous literature on the subject of masculinities in the Pacific, and especially of Melanesia. The particular focus on Melanesia is discussed in terms of the colloquia from which the papers originated and is also linked to a discussion of the regionalism of applied social science in Australia. In acknowledging the current link between academic research into gender and the aid and development industries, this introduction critically discusses how understandings of Pacific men and masculinities have presented a ‘problem’ to both of these areas. Indeed, while assessing particular instances in the changing situation of Pacific men's lives, the papers in this Issue also provide a timely critique of the shared dilemmas of anthropology and development within the region.